Microstructural evolution and solid state dewetting of epitaxial Al thin films on sapphire (α-Al2O3). (July 2017) - Hieke, S.W.; Breitbach, B.; Dehm, G.; Scheu, C.
Abstract: Solid state dewetting can be used for targeted patterning, but also causes degradation or failure of thin film devices. In this work the temperature-induced changes of a tetracrystalline model system with inhibited surface diffusion are studied. This is accomplished by growing Al thin films by molecular beam epitaxy on single crystalline (0001) oriented sapphire substrates. The as-deposited Al films form two orientation relationships ( OR I and OR II ) both subdivided in two twin-related growth variants leading to a tetracrystalline microstructure. Two processes evolve during annealing at 600 °C. Grain growth and texture evolution towards OR II occur in addition to the formation of drum-like voids in the Al film covered by a thin membrane. The surface oxide suppresses Al surface diffusion and in contrast to classical solid state dewetting interface and grain boundary diffusion dominate. High energy grain boundaries were identified as initial points of the void formation. Graphical abstract: Image 1